Music Composition: Tub Rueng Kanlayanamit - Nuyee, Pagorn; Pornprasit, Kumkom (Rangsit Music Journal, 2023)
This study is focused on the Badjakosol Music Academy with two main objectives: 1) Historiography works on biographies, composition data, and music analysis of 6 outstanding artists of the academy. 2. Creative work a new musical suite “TUB RUENG KANLAYANAMIT” based on Badjakosol style. Data in this qualitative research is conducted by interview resource persons, documentary collections, and utilizing music theory that related to Badjakosol Music Academy. The findings of the historical study show that 1) music icons of Badjakosol Music Academy are all played an essential role throughout the Rattanakosin period, and their musical abilities and knowledge are well preserved among their students from generation to generation. 2) There is a unique musical style represented in original compositions and performance techniques. However, each generation could have its own identity, which still maintains its roots. The creative composition TUB RUENG KANLAYANAMIT consists of 6 successive songs which applying three techniques of creation: 1) A new poetic song text describing the biography of 6 artists of the academy, 2) the new melodies inspired by the understanding of Badjakosol musical style, 3) the mixed singing style which apply original techniques of Khunying Paitoon Kittiwan combined with the researcher’s interpretations.